Investigation of Scutellaria radix on Phenoloxidase and Prophenoloxidase of Giant Freshwater Prawn, Macrobrachium rosenbergii, via Reverse-gavage Feeding - Andriawan, Soni; Bao, Hung Tran; Cheng, Phillip T.; Yuniarti, Ating (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2018)
Scutellaria radix is one of the ancientest approaches to treat diseases. The aim of this study was to investigate the effect of Scutellaria radix on the immune responses of Macrobrachium rosenbergii by reverse-gavage feeding and their protection against Lactococcus garvieae. In brief, M. rosenbergii was injected with S. radix water extract at 1, 5 and 10 µg/µl via reverse-gavage feeding (RGF). Phenoloxidase (PO) activity of hemocytes and prophenoloxidase (proPO) gene of hepatopancreas were assessed to determine M. rosenbergii immunity. The results revealed that the concentration of S. radix extract at 5 µg/µl enhanced significantly the phenoloxidase of M. rosenbergii correlated with the control group. For pro PO were up-regulated by all concentration in a time-dependent manner. The highest percentage of survival rates was observed at 5 µg/µlof S. radix water extract after challenged with L. garvieae. The present discoveries suggest that S. radix water extract at the concentration of 5 µg/µlmay raise the immune responses and gene expressions in M. rosenbergii using RGF.